2017
DOI: 10.5603/arm.a2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Noninvasive Ventilation Failure in Critically Ill Obese Patients: A Brief Narrative Review

Abstract: Non-invasive ventilation ( NIV ) has been used successfully for the management of acute respiratory failure (ARF) more often in the last two decades than previously. Unfortunately, NIV can have failure rates ranging from 5% to 50% and patient selection is the key to success. There are particular groups of patients that are more likely to benefit from NIV. For patients with hypoventilation syndrome (OHS) this treatment can be beneficial. This review seeks to evaluate the effectiveness of NIV in acute ARF and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…89 The factors associated with treatment failure were pneumonia, sepsis, and higher severity scores at admissions, common features of patients with ARDS. In summary, it has been suggested how noninvasive ventilation may be safely used in patients with hypercapnic acute respiratory decompensation of obesityhypoventilation syndrome, 90 whereas much more caution should be used in the case of acute hypoxemic respiratory failure and ARDS.…”
Section: High-flow Nasal Cannula and Noninvasive Ventilationmentioning
confidence: 99%
“…89 The factors associated with treatment failure were pneumonia, sepsis, and higher severity scores at admissions, common features of patients with ARDS. In summary, it has been suggested how noninvasive ventilation may be safely used in patients with hypercapnic acute respiratory decompensation of obesityhypoventilation syndrome, 90 whereas much more caution should be used in the case of acute hypoxemic respiratory failure and ARDS.…”
Section: High-flow Nasal Cannula and Noninvasive Ventilationmentioning
confidence: 99%
“…36 Higher NIV success rates were found in subjects with acute idiopathic decompensation of OHS and with high P aCO 2 levels. 33,36 Interestingly, subjects with acute-on-chronic respiratory failure had a delayed but successful response to prolonged NIV, which prevented intubation. 33,36 In our study, the median time to correct respiratory acidosis with NIV was 2.9 d, which should encourage the prolonged use of NIV when this is possible, instead of early intubation.…”
Section: Discussionmentioning
confidence: 92%
“…Studies that evaluated NIV in subjects who were obese and critically ill found NIV failure rates that ranged from 2 to 60%. 23,[32][33][34][35][36] The higher failure rates in these studies than in the current study may be explained by higher severity scores, more severe hypoxemia, and infectious pneumonia as the main reason for acute hypercapnic respiratory failure. 36 Higher NIV success rates were found in subjects with acute idiopathic decompensation of OHS and with high P aCO 2 levels.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations